Population assessment and species distribution modeling of Paris polyphylla in Sikkim Himalaya, India - DAWA LHENDUP LEPCHA; ADITYA PRADHAN; DHANI RAJ CHHETRI (Society for Indonesian Biodiversity, 2019)
Abstract. Lepcha DL, Pradhan A, Chhetri DJ. 2019. Population assessment and species distribution modeling of Paris polyphylla in Sikkim Himalaya, India. Biodiversitas 20: 1299-1305.  Paris polyphylla Smith is an important therapeutic plant that grows in the Indian Himalayan region. In Sikkim, the survival of the species is threatened by illegal extraction of its rhizome. Therefore, immediate conservation initiative is required to conserve the existing species population in the wild. Population assessment through field survey followed by ENM revealed a positive correlation between predicted suitable habitats with the actual sites of its occurrence, except in disturbed habitats. Precipitation of driest month (Bio14) and slope were the most influential factors that contributed 41.9 % and 30 % respectively to the MaxEnt model. Field survey revealed that the density of the plants varied between 0.45 (pl/m2) and 3.89 (pl/m2) and the frequency varied from 36% to 76%. The IVI for P. polyphylla ranged between 2.68 to 8.66 based on locations. On the other hand, the IVI of associated species varied from 3.57 to 18.14 based on species. P. polyphylla is a vulnerable plant in Sikkim Himalaya and it is facing an imminent threat of extinction. Under this situation, it is imperative that works on predictive modeling will help conserve the species. This study identified the potential habitats for P. polyphylla in the higher elevations of Sikkim Himalaya where it could be reintroduced.